"Damp in bathroom. Damp in back room. It's very depressing!" exploring the relationship between perceived housing problems, energy affordability concerns, and health and well-being in UK social housing. (July 2017) - Boomsma, Christine; Pahl, Sabine; Jones, Rory V.; Fuertes, Alba
Abstract: Social housing residents often struggle with achieving adequate levels of warmth in their home on a limited household budget. Additionally, other housing problems such as damp are common. Previous research has found a link between housing problems and poor health and reduced well-being, but this relationship is complex and poorly understood. A survey among UK social housing residents ( N =536) investigated the association between cold and damp housing, as well as the role of energy affordability concerns in the relationship between housing problems and health. The findings indicated that struggles with keeping warm related to a cluster of damp and mould issues rather than any one specific issue. In describing these problems householders expressed a sense of frustration and helplessness. Support was found for an indirect effect on health whereby households experiencing cold, damp or mould issues reported more difficulty with affording their energy bills, these affordability concerns in turn related to poor health and well-being. The effects were found to be more consistent and stronger for men compared to women. Policies aimed at reducing housing problems should consider the important role of affordability concerns and the need for households to regain control of their energy bills. Highlights: Housing problems common in social housing could have negative health impacts. We examine these housing problems and what may underlie the association with health. Problems with keeping warm relate to a range of condensation, damp and mould issues. Households with housing problems report more energy affordability concerns. These concerns in turn were found to relate to poor health and reduced well-being.